Evolução temporal das definições de síndrome do desconforto respiratório agudo - Fioretto, José Roberto [UNESP]; Carvalho, Werther B. de (Sociedade Brasileira de Pediatria, 2013)
OBJECTIVE: to review the evolution of acute respiratory distress syndrome (ARDS) definitions and present the current definition for the syndrome. DATA SOURCE: a literature review and selection of the most relevant articles on ARDS definitions was performed using the MEDLINE®/PubMed® Resource Guide database (last ten years), in addition to including the most important articles (classic articles) that described the disease evolution. DATA SYNTHESIS: the review included the following subjects: introduction; importance of definition; description of the first diagnostic criterion and subsequently used definitions, such as acute lung injury score; definition by the American-European Consensus Conference, and its limitations; description of the definition by Delphi, and its problems; accuracy of the aforementioned definitions; description of most recent definition (the Berlin definition), and its limitations; and practical importance of the new definition. CONCLUSIONS: ARDS is a serious disease that remains an ongoing diagnostic and therapeutic challenge. The evolution of definitions used to describe the disease shows that studies are needed to validate the current definition, especially in pediatrics, where the data are very scarce.

OBJETIVO: revisar a evolução das definições de síndrome do desconforto respiratório agudo e apresentar a proposta atual para a mesma. FONTES DOS DADOS: revisão bibliográfica e seleção de publicações mais relevantes sobre as definições de síndrome do desconforto respiratório agudo, utilizando a base de dados MEDLINE®/PubMed® Resources Guide (últimos dez anos), além da inclusão dos artigos mais importantes (artigos clássicos) que descrevem a evolução da doença. SÍNTESE DOS DADOS: revisão incluiu os seguintes tópicos: introdução; importância da definição; descrição do primeiro critério diagnóstico e das definições utilizadas subsequentemente, como o escore de lesão pulmonar aguda, definição da Conferência de Consenso Americana- Europeia e suas limitações, descrição da definição de Delphi e seus problemas; acurácia das definições citadas e descrição da definição mais recente (Definição de Berlim) e suas limitações; e importância prática da nova definição. CONCLUSÕES: a síndrome do desconforto respiratório agudo é uma doença grave, que consiste em um contínuo desafio diagnóstico e terapêutico. A evolução das definições utilizadas para descrever a doença evidencia que estudos são necessários para validar a definição atual, principalmente em pediatria, onde os dados são muito escassos.
Temporal evolution of acute respiratory distress syndrome definitions
Keywords: Síndrome do desconforto respiratório agudo; Lesão pulmonar aguda; Crianças; Definição; UTI Pediátrica; Acute respiratory distress syndrome; Acute lung injury; Children; Definition; Pediatric ICU